Progestin vaginal administration - Chełmicki, Artur; Skrzypulec-Plinta, Violetta; Chełmicki, Zbigniew (Menopause Review/Przegląd Menopauzalny, 2010)
Progesterone is an essential regulator of the normal female reproductive function in the uterus, ovary, mammary gland and brain. It also plays an important role in non reproductive tissues such as the cardiovascular system, bone and central nervous system. Progesterone supplementation is associated with the risk of various adverse effects. It is vital to maximize compliance in order to achieve full therapeutic success. Endometrial progesterone concentration levels vary according to the administration route. Many experimental and clinical studies support the hypothesis that progesterone administered vaginally is distributed selectively to the uterus. This phenomenon leads to higher progesterone tissue concentrations with simultaneously lower systemic circulation concentrations. This paper aims to review current literature describing various aspects of progesterone and progestin distribution with respect to the administration route. Special interest was given to explain different mechanisms leading to higher endometrial concentrations described as “first uterine pass effect”. We summarized data that support various theories of vaginal-uterine progesterone transport, including direct diffusion through tissue, absorption into venous/lymphatic circulatory system and countercurrent vascular exchange with diffusion from utero-vaginal veins and lymph vessels to arteries. A lot of evidence in the international and Polish literature shows that vaginal progesterone administration seems to be effective in miscarriage, luteal support and menopause treatment as well as preterm birth prevention.